Pengaruh Lama Waktu Biofermentasi Chromolaena Odorata dengan Sumber Karbon Tepung Putak terhadap Kandungan Serta Kecernaan Protein Kasar dan Lemak Kasar In vitro - Nomleni, Meri; Dami Dato, Twen O.; Lestari, Gusti A. Y.; Mullik, Marthen L. (Animal Agricultura, 2025)
The purpose of this study was to determine the effect of the length of biofermentation time of chromolena odorata with a carbon source of putak flour on the content and digestibility of crude protein and crude fat in vitro. The research method used is an experimental method (experimental) with a Complete Random Design pattern consisting of 4 treatments and 4 repeats so that there are 16 experimental units. The treatment used is LB21: biofermentation duration 21 days (As control), LB14: biofermentation duration 14 days, LB7: biofermentation duration 7 days, LB0: biofermentation duration 0 days. The data were obtained and analyzed by variety analysis (ANOVA), and continued with the Duncan multiple distance test to determine the effect between treatments. The results of statistical analysis showed that the length of biofermentation of Chromolaena odorata with the carbon source of putak  flour had a real effect (P<0,01) On crude protein content, crude fat content and crude protein digestibility in vitro, while on crude fat digestibility in vitro the effect is not real (P<0,05). It can be concluded that the length of biofermnetation of Chromolaena odorata with putak flour source affects crude protein content, crude fat and gauze protein digestibility in vitro but does not affect crude fat digestibility in vitro.